1984
DOI: 10.1144/gsl.sp.1984.017.01.67
|View full text |Cite
|
Sign up to set email alerts
|

Neogene to Quaternary geodynamics of the area of the Ionian Sea and surrounding land masses

Abstract: Summary Investigations in the north-eastern and central Ionian Sea document important palaeogeographic and palaeoceanographic changes since Neogene time. These findings support the model of shallow basinal evaporation during Messinian time. On this basis the rate of subsidence of the Ionian Sea is calculated for the last 6 Ma, at about 1 m per 1000 years for basinal settings and half this for marginal settings. Elevated terraces corresponding to high glacio-eustatic stages in the Quaternary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Separation between the Pomatoschistus line and that forming the precursor for the two other genera may be envisaged to have occurred in the middle Miocene Serravalian (12-14 mya), with enclosure of the brackish Sarmatic Sea and the beginning of the evolution of the Ponto-Caspian endemic fauna (Steininger & Rogl, 1984), involving onset of canal loss in the latter line. Separation between Knipowitschia and Economidichthys may be linked with the Upper Miocene Messinian salinity crisis, affecting the Mediterranean basins from about 6.5 mya (Van Couvering et al, 1976), and noted for the Ionian Basin in particular by Fabricius (1984). With elimination of more stenohaline marine Pomatoschistus under hypersaline evaporative conditions, the spread of euryhaline Sarmatic fauna into the eastern basin may have become possible, and the pre-existing physiological capability to tolerate euryhaline conditions, noted in most recent Knipowitschia, would have favoured this process (Mordukhai-Boltovskoi, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Separation between the Pomatoschistus line and that forming the precursor for the two other genera may be envisaged to have occurred in the middle Miocene Serravalian (12-14 mya), with enclosure of the brackish Sarmatic Sea and the beginning of the evolution of the Ponto-Caspian endemic fauna (Steininger & Rogl, 1984), involving onset of canal loss in the latter line. Separation between Knipowitschia and Economidichthys may be linked with the Upper Miocene Messinian salinity crisis, affecting the Mediterranean basins from about 6.5 mya (Van Couvering et al, 1976), and noted for the Ionian Basin in particular by Fabricius (1984). With elimination of more stenohaline marine Pomatoschistus under hypersaline evaporative conditions, the spread of euryhaline Sarmatic fauna into the eastern basin may have become possible, and the pre-existing physiological capability to tolerate euryhaline conditions, noted in most recent Knipowitschia, would have favoured this process (Mordukhai-Boltovskoi, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…The timing of inversion is restricted to latest Miocene (Tortonian) in relation with a plate reorganization preceding the main phase of opening of the Tyrrhenian Basin (Chamot-Rooke, Rangin, et al, 2005;Gallais et al, 2011), and probably not Late Cretaceous to Paleogene as suggested by Roure et al (2012). The same structures were interpreted as Late Miocene tilted blocks evidencing extension of the African plate (e.g., Hieke et al, 2003Hieke et al, , 2009), suggesting very recent formation of the basin (Fabricius & Hieke, 1977;Fabricius, 1984; Figure 2).…”
Section: Geodynamic Scenarios: Geological and Paleomagnetic Constraintsmentioning
confidence: 96%